Risk factors on length of stay among pulmonary tuberculosis patients: A systematic review and meta-analysis - Dao Weiangkham; Adinat Umnuaypornlert; Surasak Saokaew; Neeranuch Wongcharoen; Samrerng Prommongkol; Jutamas Ponmark (International Journal of Nursing Studies Advances)
Background: Pulmonary Tuberculosis (PTB) remains a pressing public health concern. Long hospital stays for PTB patients can overburden both patients and healthcare systems. Objective: To identify the key factors contributing to extended length of stay in PTB patients. Information sources: Four electronic databases (PubMed, Scopus, Embase, and CINAHL) were systematically searched from inception to January 1, 2023. Methods: The articles were screened and performed according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Inclusion criteria were PTB patients diagnosed by doctors and studies reporting factors affecting length of stay. Exclusion criteria were review articles, case study, conferences abstract, and proceedings. Study quality was assessed using the Newcastle-Ottawa Scale (NOS). A random-effects model was used to analyzed risk factors for length of stay. Heterogeneity was employed using I2 and Q statistics. Forest plots displayed effect sizes (ES) and 95 % confidence intervals. STATA 14.2 was used for meta-analysis. Results: A total of 1,190 studies were screened from reputable electronic databases, six studies comprised of 9,231 participants were included. Meta-analysis revealed that they are six risk factors associated with longer length of stay including; older age (OR 1.50, 95 % CI 1.07–2.09, p = 0.019), comorbidity (OR 1.44, 95 % CI 1.17–1.78, p = 0.001), HIV patient (OR 1.40, 95 % CI 1.16–1.69, p = 0.001), patients with ADR (OR 2.19, 95 % CI 1.47–3.26, p < 0.001), MDR TB (OR 3.16, 95 % CI 2.31–4.32, p < 0.001), and miliary TB (OR 1.37, 95 % CI 1.10–1.70, p = 0.004) with minimal heterogeneity [(I2 = 34.2 %, p = 0.207), (I2 = 43.1 %, p = 0.118), (I2 = 0.0 %, p = 0.573), (I2 = 0.0 %, p = 0.723), (I2 = 0.0 %, p = 0.366), and (I2 = 0.0 %, p = 0.753), respectively]. There was no evidence of publication bias according to Begg's and Egger's test. Conclusions: In conclusion, six risk factors were identified as significantly associated with longer hospital stays in PTB patients: older age, comorbidities, HIV infection, ADR, MDR-TB, and miliary TB. These findings highlight the importance of targeted interventions for these high-risk groups to reduce length of stay and alleviate the burden on healthcare systems. The results are based on a meta-analysis of six studies with minimal heterogeneity, and no evidence of publication bias was found. Future research should focus on exploring additional factors influencing length of stay, particularly in diverse populations, and evaluating the effectiveness of interventions to shorten hospital stays. Additionally, studies examining the impact of healthcare infrastructure and resource allocation on length of stay could provide valuable insights for improving patient outcomes. Registration: This study was registered with PROSPERO, CRD4203390615